2018
DOI: 10.3389/fmed.2018.00286
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Manofluorographic Study in Patients With Multiple System Atrophy: Possible Early Detection of Upper Esophageal Sphincter and Proximal Esophageal Abnormality

Abstract: Introduction: Multiple system atrophy (MSA) has detrimental effects on swallowing function. The swallowing function of patients with MSA has not been systematically characterized and the underlying pathophysiological mechanisms of dysphagia remain poorly understood.Objectives: To investigate the characteristics of swallow function in MSA using high-resolution manofluorography (HRMF).Methods: We conducted a retrospective review of twenty-five MSA patients who underwent HRMF from 2016 to 2017. HRMF was utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…In cases of pharyngeal dysphagia, impaired UES relaxation often occurs in Parkinson's disease and MSA (3, 7). Inadequate duration of UES relaxation and abnormal hyper-pressure of the resting UES are often recognized in patients with MSA regardless of the MSA type (4, 7). Impaired laryngeal elevation and reduced pharyngeal contraction can often be observed in patients with ALS resulting from weakness of the pharyngeal muscles with disease progression (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of pharyngeal dysphagia, impaired UES relaxation often occurs in Parkinson's disease and MSA (3, 7). Inadequate duration of UES relaxation and abnormal hyper-pressure of the resting UES are often recognized in patients with MSA regardless of the MSA type (4, 7). Impaired laryngeal elevation and reduced pharyngeal contraction can often be observed in patients with ALS resulting from weakness of the pharyngeal muscles with disease progression (5).…”
Section: Discussionmentioning
confidence: 99%
“…The videofluoroscopic swallowing study (VFSS) showed no apparent impairment in the oral phase of swallowing, although mild dysarthria was observed. High-resolution manofluorography (HRMF) showed deficient relaxation of the UES during swallowing and abnormal deglutitive proximal esophageal contraction (Figure 1B) (4). To secure an air way and maintain it clear, aspiration prevention surgery was considered.…”
Section: Case Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the oropharyngeal phases of swallowing are most impaired in MSA, subtle esophageal dysmotility may also occur. Main dysfunctions observed by means of VFSS and high-resolution manometry, even in patients who were asymptomatic, included food stagnation in the esophagus, reduced esophageal peristalsis, hypomotility of the distal esophagus, abnormally high upper esophageal sphincter (UES) pressure and uncoordinated proximal esophageal contraction pressure during swallowing and resting [23,27,28].…”
Section: Diagnosis Of Dysphagia In Msamentioning
confidence: 99%
“…Previously ADPEC was defined as abnormal hypertensive and discoordinated abnormal proximal esophageal contraction during swallowing evaluated by HRMF 14 (Fig. 1).…”
Section: Abnormal Deglutitive Proximal Esophageal Contractionmentioning
confidence: 99%